A New Version of the MADAAMI Method for Assessing Lower Limb Alignment during Demi-Plie, Grand Plié, and Fondu. Issue 3 (September 2018) - Gontijo, Kaanda Nabilla Souza; Candotti, Claudia Tarrago; do Amaral, Maiane Almeida; dos Santos, Gabriela Cristina; Williams, Valerie; Loss, Jefferson Fagundes
The MADAAMI (Método de Avaliação Dinâmica do Alinhamento Articular dos Membros Inferiores—Dynamic Evaluation Method of Lower Limb Joint Alignment) is an instrument that has been developed and validated with the aim of providing direct, simple, and practical support for the identification of compensations and misalignments of joints. The first version of the instrument had some limitations. The goals of the present study are to update the instrument (MADAAMI-II), evaluate its content validity, and verify inter-rater and intra-rater reproducibility during the execution of demi-plié, grand plié, and fondu in two turnout positions of classical ballet (120° and self-reported) and in parallel foot position. The study was approved by the local university's Ethics Committee, and 20 ballet dancers from different levels of the Bolshoi Theater School in Brazil participated. Each dancer was digitally recorded executing the three steps in the different foot positions. To verify inter-rater reproducibility, three independent raters used the MADAAMI-II's score sheet. To verify intra-rater reproducibility, a single rater repeated the evaluation after a 7-day interval. Cohen's Kappa Coefficient (a = 0.05) was used. The results showed kappa values ranging from 0.062 to 0.357 in the inter-rater reproducibility analysis and from 0.431 to 0.806 in the intra-rater reproducibility analysis. We concluded that MADAAMI-II is, due to its practicality, valid, reproducible, and suitable for use by the same rater engaged in the classical ballet teaching-training process.